2014
DOI: 10.1111/gove.12120
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Corruption: The Mediating Power of Institutional Logics

Abstract: Scholars have argued that recruiting more women to office is an effective way to curb corruption; however, the more precise mechanisms underlying why this may be the case have remained unclear. We use meso-level theories to elaborate on the relationship and suggest that institutional logics mediate the effect of gendered experiences on corruption. We make two propositions: First, we suggest that the relationship between more women and lower levels of corruption is weaker in the state administration than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 31 publications
(46 reference statements)
0
45
0
1
Order By: Relevance
“…More recent studies have convincingly shown that the correlation between the proportion of women in parliament and national levels of corruption is stronger in democracies than in authoritarian states (Esarey & Chirillo 2013) and that, even within democracies, the correlation is stronger within the electoral arena than in other branches of government (Stensöta et al 2015). Contemporary research on the link between women's representation and levels of corruption tends to follow and expand on the suggestion by Swamy et al (2001) that women reduce corruption since they are, on average, more riskaverse than men.…”
Section: Women's Representation and Corruptionmentioning
confidence: 99%
“…More recent studies have convincingly shown that the correlation between the proportion of women in parliament and national levels of corruption is stronger in democracies than in authoritarian states (Esarey & Chirillo 2013) and that, even within democracies, the correlation is stronger within the electoral arena than in other branches of government (Stensöta et al 2015). Contemporary research on the link between women's representation and levels of corruption tends to follow and expand on the suggestion by Swamy et al (2001) that women reduce corruption since they are, on average, more riskaverse than men.…”
Section: Women's Representation and Corruptionmentioning
confidence: 99%
“… Beyond decreasing corruption, several countries across Latin America have established women's police units to improve reporting of crimes against women, offer support to female victims, and to raise awareness around women's security issues (UN Women, ). If laws are passed to protect underrepresented groups such as women or minorities, this may engender citizen trust in the government (Swamy et al, ; Stensöta et al, ; Watson & Moreland, ). Thus, to the extent that women are recruited into police forces to protect the rights of women, the representation of women's interests may serve as a fourth possible mechanism through which increases in female police officers improve perceptions of corruption.…”
mentioning
confidence: 99%
“… For an exception, see Stensöta, Wängnerud, and Svensson (), who focus on officials in bureaucracies.…”
mentioning
confidence: 99%
“…For an exception, seeStens€ ota, Wängnerud, and Svensson (2015), who focus on officials in bureaucracies.2 Corruption might also have an indirect negative influence, in that it affects women's resources to compete for office Stockemer (2011). pinpoints that corrupt societies grant fewer educational and financial opportunities to women and, therefore, tend to have a smaller pool of eligible female candidates (see alsoGoetz, 2003).…”
mentioning
confidence: 99%